THE EFFECT OF WATCHING CARTOON MOVIES THAT CONTAIN ELEMENTS OF VIOLENCE AGAINST AGGRESSIVE BEHAVIOR IN PRIMARY SCHOOL STUDENTS - Maria Friska Nainggolan, Robinson Hutagaol, Yetti Rosmawati Panggabean, Serly Ondina (Pusdikra-Publishing.com, 2020)
Aggressive behavior is an action that aims to injure another person verbally or non-verbally, physically or non-physically. This research aims to determine and describe forms of aggressive behavior in elementary school children and also the factors that cause aggressive behavior to emerge. The subjects in this research were 5 elementary school children, 4 teachers, and 5 family members closest to the children. Data collection techniques using semi-structured interviews and observation, data analysis using narrative descriptive analysis techniques. The results of this research are that the forms of aggressive behavior carried out by each child differ in verbal aggression, such as shouting, speaking harshly, threatening, shouting, talking to themselves when other people are talking. Physical aggression in the form of grabbing, pinching, pushing, hitting, throwing, tickling, stepping on, slapping, tripping. Factors that cause children to behave aggressively come from within the individual (internal), namely innate behavior since the child was born. Children carry out aggressive behavior when they want something or when they are prohibited from doing things that the child likes, resulting in feelings of anger and hostility. Factors from outside the individual (external), namely in the form of family factors, school factors and cultural factors.